Geochemistry of the Annidale Group: implications for the tectonic setting of Lower Ordovician volcanism in southwestern New Brunswick - MacLeod, M.; Winchester, J.; Ruitenberg, A. (Atlantic Geology)

(untitled) (Atlantic Geoscience Society, 1994)
Chemical analyses from volcanic rocks in the Lower Ordovician Annidale Group in southern New Brunswick indicate that it contains two main suites. The volumetricalry more abundant suite is bimodal, and consists of within-plate tholeiitic basalt and myolite. The other suite contains rocks that exhibit features indicative of oceanic or possibly subduction-related magmatism. The chemistry of the former suite is consistent with the current interpretation that Ordovician volcanism in southwestern New Brunswick occurred in a back-arc basin. The latter suite, situated near the highly-sheared southeastern margin of the Annidale Group, apparently contains remnants of a different magmatic series near the suture zone between the Gander Zone and the surface expression of the Avalon Zone to the southeast.